The emerging tumor microbe microenvironment: From delineation to multidisciplinary approach-based interventions - Yu Fu; Jia Li; Wenyun Cai; Yulan Huang; Xinlong Liu; Zhongyi Ma; Zhongjie Tang; Xufei Bian; Ji Zheng; Jiayun Jiang; Chong Li (Acta Pharmaceutica Sinica B, 2024)
Intratumoral microbiota has become research hotspots, and emerges as a non-negligent new component of tumor microenvironments (TME), due to its powerful influence on tumor initiation, metastasis, immunosurveillance and prognosis despite in low-biomass. The accumulations of microbes, and their related components and metabolites within tumor tissues, endow TME with additional pluralistic features which are distinct from the conventional one. Therefore, it's definitely necessary to comprehensively delineate the sophisticated landscapes of tumor microbe microenvironment, as well as their functions and related underlying mechanisms. Herein, in this review, we focused on the fields of tumor microbe microenvironment, including the heterogeneity of intratumor microbiota in different types of tumors, the controversial roles of intratumoral microbiota, the basic features of tumor microbe microenvironment (i.e., pathogen-associated molecular patterns (PAMPs), typical microbial metabolites, autophagy, inflammation, multi-faceted immunomodulation and chemoresistance), as well as the multidisciplinary approach-based intervention of tumor microbiome for cancer therapy by applying wild-type or engineered live microbes, microbiota metabolites, antibiotics, synthetic biology and rationally designed biomaterials. We hope our work will provide valuable insight to deeply understand the interplay of cancer-immune-microbial, and facilitate the development of microbes-based tumor-specific treatments.